The great masquerade: A rapidly growing pulmonary nodule. Issue 6 (8th December 2022) - Mullin, Monica; Mehta, Arjun; Van Eeden, Stephanus; Leung, Janice
Abstract: We present a case in which the patient had left-sided chest pain and was found to have an enlarged spleen with a necrotic mass and multiple pulmonary nodules. The splenic biopsy was nondiagnostic and repeat imaging showed rapid enlargement of the pulmonary nodules with high standardized uptake value (SUV) uptake. Spindle cells present on the lung pathology initially led to the diagnosis of sarcomatoid lung cancer. However, further review showed CD20 staining on the specimen and the final diagnosis was diffuse large B-cell lymphoma (DLBCL), spindle cell variant. The patient was successfully treated with rituximab, cyclophosphamide, hydroxydaunorubicin hydrochloride, vincristine and prednisone (R-CHOP) after the diagnosis was confirmed. This is a very rare form of DLBCL that is commonly misdiagnosed and is often not on the differential for spindle cell tumors. To our knowledge, DLBCL spindle cell variant has never presented or been diagnosed from pulmonary nodules.